Debating the Canon: A Reader from Addison to Nafisi - Morrissey, Lee.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2005)
Over the past two decades, the debate over the 'Great Books' has been one of the key public controversies concerning the cultural content of higher education. Debating the Canon provides a primary-source overview of these ongoing arguments. Many of these contributions to this debate have achieved 'canonical' status themselves; through the focus on the canon, the full spectrum of approaches to literary studies can be seen in the essays. Therefore, this collection places the recent debate within a larger context of literary criticism's development of a canon, going back to the eighteenth century.
Keywords: Literature; Literature -- Philosophy; Literature -- History and criticism; Structural geology; Higher education; Literature; Literary Theory; Literary History; Higher Education; Structural Geology; Electronic books